La croisière dans l’espace polynésien : jeux de lieux et d’acteurs, pratiques, aménagements et enjeux de développement - Caroline Blondy (Études Caribéennes)
Cruise in French Polynesia is a rather little developed and fragile practise. The distance, the lack of infrastructures, the lack of flexibility of the rules was pointed for a long time to explain its difficulties. The analysis of cruise in French Polynesia is difficult because it includes diversified practices as in their forms, the profile of the tourists, the explored places, and social and economic impacts. Cruise seems to become one of the axes of tourist development policies set by the local government. Papeete is in the heart of developments which have also served cruise and strengthened the “urbanity” of this city.